GAMBARAN TINGKAT GEJALA DEPRESI PADA REMAJA YANG TINGGAL DI PANTI ASUHAN YAYASAN PENYANTUN ISLAM ACEH SEUTUI BANDA ACEH - Khatab Khatab; Mursyida Mursyida (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Depression is an emotional condition that is commonly characterized by deep sadness, hopelessness and guilt, withdrawal from others, being unable to sleep, loss of appetite, sexual desire, passion, and pleasure in doing daily activities. There are 350 millions of people who suffer from this mental disorder. Each year, there are 8 millions of people who commit suicide due to depression. This occurrence of depression is mostly experienced by adolescent. The increase in the symptom level of depression is also known in the orphanage. The objective of this study is to figure out the level of depression suffered by the adolescents, both male and female, who live in the Yayasan Penyantun Islam Aceh Setui Banda Aceh orphanage center, Setui, Banda Aceh. This study employed the quantitative approach by means of cross sectional survey design conducted on 51 adolescents aged 12-16 years old from December 2016 to June 2017. The data of this study was obtained by utilizing Depression Anxiety Stres Scale (DASS) questionnaire adopted consisting of 14 questions. This study reveals that there were 20 adolescents (39.2%) who were categorized as having the normal level of depression, while 2 adolescents (3.9%) suffered a low level of depression. Moreover, 9 adolescents (17.6%) experienced moderate level of depression, 14 adolescents (7.8%) suffering high level of depression, and 16 adolescents (31.4%) having very high level of depression. Based on the sexes, it can be understood that male adolescences living in this orphanage center were 25 people with 5 of them suffering the normal level of depression, none with low depression, 6 of them with moderate depression, 1 person having heavy depression, and 13 people with very heavy depression. The female respondents were 26 people with 15 of them having 15 people, 2 people having low depression, 3 people suffering moderate depression, 3 people with heavy depression, and 3 people with very heavy depression. Keywords: The symptom level of depression, DASS Quistionare, adolescent, orphanage center